Prihodnost rehabilitacije ljudi po amputaciji uda ter protetike in ortotike - Burger, Helena (Rehabilitacija (Ljubljana), 2009)
The article shortly presents the current state in the field of prosthetics, orthotics and rehabilitation of people after amputation as well as it main limitations. The latter serve as the basis for further thoughts about its development in the future. The article discusses separately the development of rehabilitation of people after upper and lower limb amputation, orthotics and accessibility of novelties.
Keywords: protetika; ortotika; rehabilitacija; vocational rehabilitation; amputacija